The Application of the Character Values of the Local Sipakatau Sipakainge Sipakalebbi to Enhance Students' Empathy through the Rational Building Model - Asmaul Husnah Amiruddin; Dadang Sundawa; Neiny Ratmaningsih (Universitas Pendidikan Mandalika, 2023)
This research aims to analyze the application of the character values of the local Sipakatau Sipakainge Sipakalebbi (3S) to enhance student empathy in Social Sciences through the rational building model. The research method used was experiment quasi with a noninvasive or non-equitable control group design. This research used a questionnaire and an observation sheet as instruments that have been tested for validity and reliability. Data analysis used the prerequisite test, namely the normality and homogeneity tests, and hypothesis testing using the paired sample t-test analyzed using SPSS For Mac 25. Based on this study's results, applying the character values based on the local Sipakatau Sipakainge Sipakalebbi (3S) through the rational building model in Social Science lessons can enhance the student's empathy. The research revealed that applying Sipakatau Sipakainge Sipakalebbi (3S) local prudence values through the modeling rational building is well applicable. Based on pre-test and post-test results, students' empathy in the experimental class is enhanced to the